2018
DOI: 10.1021/acscatal.8b00017
|View full text |Cite
|
Sign up to set email alerts
|

Parallelized Reaction Pathway and Stronger Internal Band Bending by Partial Oxidation of Metal Sulfide–Graphene Composites: Important Factors of Synergistic Oxygen Evolution Reaction Enhancement

Abstract: The electrocatalytic performance of transition metal sulfide (TMS)− graphene composites has been simply regarded as the results of high conductivity and the large surface/volume ratio. However, unavoidable factors such as degree of oxidation of TMSs have been hardly considered for the origin of this catalytic activity of TMS−graphene composites. To accomplish the reliable application of TMS-based electrocatalytic materials, a clear understanding of the thermodynamic stability of TMS and effects of oxidation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(94 citation statements)
references
References 54 publications
2
90
1
1
Order By: Relevance
“…The formed Co−O groups was further transformed to Co‐OOH species with the increase of potential, in which the Co‐OOH species could contribute to the superb catalytic performance ,. This result is well consistent with the previously reported phenomenon that the Co‐OOH would appear in high potential range during OER , . It is also notable that beyond 1.7 V, the peak intensities of both Co−O and Co−OOH bonds were diminished.…”
Section: Methodssupporting
confidence: 91%
“…The formed Co−O groups was further transformed to Co‐OOH species with the increase of potential, in which the Co‐OOH species could contribute to the superb catalytic performance ,. This result is well consistent with the previously reported phenomenon that the Co‐OOH would appear in high potential range during OER , . It is also notable that beyond 1.7 V, the peak intensities of both Co−O and Co−OOH bonds were diminished.…”
Section: Methodssupporting
confidence: 91%
“…The lower overpotential and smaller Tafel slope of NiFeNSC catalyst indicated that NiFeNSC presented better electrical transport and faster reaction kinetics than other catalysts in this study. [18] The turnover frequency (TOF) value of NiFeNSC was higher than that of NiNSC and NiFeC, suggesting the superior catalytic activity toward OER (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…[16,17] For instance, Han et al synthesized Co 1-x Ni x S 2graphene composite, and the CNS-NGA (Ni-doped CoS 2 integrated with nitrogen-doped reduced graphene) showed a much lower overpotential (330 mV at 10 mA cm À 2 ) than CNS (Ni-doped CoS 2 ), which benefited from the three-dimensional (3D) porous structure with a large surface area. [18] However, for graphene-based catalyst, since the number of active groups is limited, the bonding of the metal catalysts with graphene is weak, which prevented the metal catalyst from dispersing homogeneously, and give the resulted electrocatalyst poor stability. In addition, graphene-based composite electrodes often suffer from a low mass activity because the two-dimensional (2D) graphene sheets tend to exhibit ineffective packing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Precious-metal-based electrocatalysts exhibit the highest catalytic activity to reduce the overpotential requirement, but the high cost, scarcity and low stabilityo ft hesec atalysts have hindered their widespread application greatly. [6][7][8][9][10][11][12] Therefore, substantial efforts have been devotedt od evelop highly efficient and inexpensive materials by reducing the noblem etal usage or by exploring viable alternatives. [7,8,[13][14][15][16][17][18][19][20] There are two common approaches to enhance the activity of an electrocatalyst: ( 1) by increasing the quality of each active site (e.g.,n ormally by modulating the electronic configuration) and (2) by increasing the number of active sites at as pecific mass loading and electrode area (e.g., by engineering the structure and morphology to expose more active sites).…”
Section: Introductionmentioning
confidence: 99%